Maximets O. N. The forming of word bulding structure of subjects with desiqnate processes connected with professional and workinq activity of a man - Maximets O. N. (Philological Treatises, 2020)
In a modern Ukrainian language among the nouns with general word-building meaning “verbalnouns” there is a group of such nouns which designate processes connected with professional and working activity of a man. Suffixless – “-нн(я)”, ”-інн(я)”, ”-л(я)”, ”-к(а)”, ”-иц(я)” ”-ств(о)”, ”-ур(а)” belong to such formations in Ukrainian language. History of establishment and development of these lexical and wold-building types is the subject of our investiqation.